Assessment of apostierial professional risk for employees of metallurgical manufacturers employed in hazardous labor conditions - Sharavara, L. P.; Шаравара, Лариса Павлівна; Tishenko M. (Czech Republic, Karlovy Vary – Ukraine, Kyiv, 2018)
Introduction: The current issue of labor medicine at the present stage of its development is the evaluation of risk factors in the production, assessment of the degree of connection between their levels with health disorders, the allocation of professionally conditioned forms of disease for the further development of measures for the preservation of health.
Keywords: тези